Effectiveness of endo-vascular treatment in carotid artery stenosis: A single center study (Annals of Medical Research, 2021)
Aim: To investigate the safety and effectiveness of endo-vascular stents to treat carotid artery stenosis (CAS).Material and Methods: One-hundred fourteen patients who underwent selective endo-vascular stenting following selective carotid angiography between 2000 and 2014 were analyzed retrospectively. Demographic characteristics; stenosis degree; stent type; use of anti-coagulants and embolism protection system (EPS) during the procedure; pre-dilation and post-dilation during the procedure; use of a vascular occlusion device after the procedure; early complications (30 days); prevalence of re-stenosis of the stent; sixth-month, first-year, second-year, and fifth-year controls; radiologic imaging results; and discharge time were analyzed.Results: Among the patients, 83 (72.8%) were males and 31 (27.2%) were females, and the age range was 41–86 years (mean age: 69±8.7 years). The proportion of concurrent hypertension was higher among females with CAS (p 0.01). The proportion of early complications was higher among the patients with the Nitinol stent than among those with the Wall stent (p = 0.062). Embolic events and infarct development were observed in 13 (11.4%) patients within the first 30 days. Occlusion was detected in 4 of 97 patients (4.1%) who represented controls. While less than 50% stenosis that did not require intervention developed in four (4.1%) patients, more than 50% stenosis was detected in three (3.09%) patients. The likelihood of not developing stenosis was found to be 98% at the end of the first year, 96% at the end of the second year, and 87% at the end of the fifth year. The mean duration of stenosis was 4.86±0.11 years.Conclusion: The proportions of potency and early complications in endo-vascular treatment applied for CAS were similar to those in the literature. Further studies with a larger patient number and a longer duration of follow-up would provide better data concerning the effectiveness of treatment and complications. Keywords: Carotid artery; stenosis; stenting.
Keywords: Carotid artery; stenosis; stenting.